Development of Hybrid Choice Models for Modal Shift Study: A Case Study of MRT Green Line Extension Kasetsart University Station - อัตตาภิบาล, ณัฐชนน (Srinakharinwirot University Engineering Journal, 2018)
This research is aimed at developing a hybrid choice model to forecast the proportion of modal shift from private car to mass rapid transit (MRT) with either campus feeder buses or motorcycle taxis as egress modes of commuting trips to Kasetsart University. A survey of stated preference and factor scoring of four latent factors including convenience, comfort, safety and reliabilities are conducted. The results show that the newly developed hybrid choice model which integrates the traditional modal choice model with the MIMIC model can provide more accurate forecasting results than the traditional one that considering only travel time and cost subject to the increase of McFadden’s R-Square statistics by 4.03% and 3.26%, respectively where the precision of model predictions is increased by 0.74% and 0.68%, respectively.